PENGARUH PROBLEM BASED LEARNING BERBASIS HIGHER ORDER THINKING SKILL (HOTS) TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS - Fitri, Anisa; Sari, Astrid Chandra; Rosita, Jamiati (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This research is a descriptive quantitative research that aims to find out how the influence of the Problem Based Learning learning model on the critical thinking mathematics ability of students on social arithmetic material. The research was carried out at SMP Negeri 2 Balen, with the selection of class VII D as an experimental class with a total of 32 students and VII F as a control class with a total of 33 students. The method used is experimental research. Data collection techniques in this study were through observation, documentation and test techniques. Data analysis in this study used descriptive analysis and inference which included normality test, homogeneity test and hypothesis test (independent sample t-test) using the SPSS statistical application program version 26 with a significant level of 5%. The calculation of the independent sample t-test obtained a signification value (2-tailed) of 0.000 < 0.05 and the calculation of the gain score obtained a value of 0.7081. The results of this study show that the Problem Based Learning learning model has a significant influence on the critical thinking ability of students with the category of improvement being high.